Spreadsheets as a Complementary Tool in Textual Criticism: An Example from Cicero - Rozzi, Stefano (Ciceroniana On Line, 2021)
Since the first electronic calculators were invented, philology has come to exploit the enormous potential of calculation for simplifying its studies and above all for speeding up the collation of manuscripts. In this way, table systems, automatic collation and statistical calculation software were experimented by applying techniques already used for medical studies. However, many of these systems present some difficulties for a user with a limited knowledge of the world of informatics, because often their functionality is based on computer programming languages, or they require the entire transcription of the text(s) that leads to a not insignificant expenditure of time. In order to combine the philologist’s computing needs and to make the use of IT tools easier even for the less experienced scholars, A system of collation that exploits the potential of spreadsheets (e.g. Microsoft Excel, OpenOfficeCalc etc.) is proposed. Such a system is not limited further by the creation alone of tables with textual contents. Instead, the textual data is exploited when converted into numerical data for orienting the appropriate studies, succeeding in processing thousands of data points in few steps and greatly simplifying collation and stemmatic reconstruction. This study is an introduction to a system that will be expanded with additional tools and deepened in forthcoming publications.